Synthesis of new azo dyes via Suzuki coupling - Khadim, Ali G. (Al-Qadisiyah Journal of Pure Science, 2017)
The synthesis of new azo dyes have been achieved by coupling reaction of pyrimidine derivative with different phenolic compounds , the products have been treated with 2- fluoro boronic acid by Suzuki coupling reaction to give new azo dyes . These compounds have been characterized by spectroscopic methods (FTIR , UVVIS) ,TLC and melting point .